Income elasticity for animal-based protein and food supply - Diana Kmeťková; Milan Ščasný (Charles University in Prague, Institute of Economic Studies (IES), 2022)
Dietary choices are one of the main causes of mortality and environmental degradation. Plant-based diets, in comparison to diets rich in animal products, are considered to be more sustainable because they use fewer natural resources and come with a lower environmental burden, resulting in lower greenhouse gas emissions in particular. However, the rapid increase in global population and wealth has led to an increased demand for foods of animal origin. Getting enough protein might be one of the reasons people consume animal products but its increased consumption could negatively impact our health and environment. Hence, the aim of this paper is to examine the economic and sociodemographic factors that influence the amount and the share of animal food intake as well as the amount and the share of animal-based protein in the worldwide diet. An econometric analysis of country-level panel data allows us to investigate the Environmental Kuznets Curve hypothesis in the context of a sustainable diet. The findings suggest that the relationship between GDP per capita and animal-based food and protein supply resembles an inverted U-shaped curve. In the global analysis, the turning point is estimated to be around 81,500 in relation to both the share of animal food supply and the share of animal proteins. The resulting income elasticity shows to be inelastic across the domain, however, the specific values vary depending on the country's level of GDP. The elasticity is positive for low- to middle-income countries with its maximum of 0.29; and it becomes negative once a country reaches a GDP level of about 77,000- 81,000.
Keywords: Q11; Q56; C33; C52; O13; 330; GDP; Environmental Kuznets curve; animal consumption; animal protein; healthy and sustainable diet; panel data analysis